Nitrogen catabolite repression of the L-asparaginase of Bacillus licheniformis. - Golden, K J (1985)
We report the presence of a single L-asparagine aminohydrolase activity (EC 3.5.1.1) in extracts of Bacillus licheniformis A5. The synthesis of the enzyme was apparently under nitrogen catabolite repression control.